The Political Economy of Highly Pathogenic Avian Influenza in Cambodia - Ear, Sophal (International Journal of Poultry Science, 2010)
This study investigates the political economy of policy processes surrounding the response to Highly Pathogenic Avian Influenza (HPAI) in Cambodia, identifying key actors, networks, associated narratives and practices of policy. With the emergence and spread of HPAI in Cambodia in 2004, international donors and governments intervened in their self-interest in supplying foreign aid in order to control the outbreak as an emergency response to a global health threat. Although the outbreak subsided in 2007 with the assistance of foreign aid, the livelihood of those affected was inadequately addressed. Because 90 per cent of Cambodian poultry is raised in backyards, almost anything achieved with poultry (or livestock) can be considered pro-poor, but this, regrettably, is not of particular interest do donors.